One Place Doesn't Fit All: Improving the Effectiveness of Sustainability Standards by Accounting for Place - Jablonski, Kevin E.; Dillon, Jasmine A.; Hale, James W.; Jablonski, Becca B. R.; Carolan, Michael S. (Frontiers in Sustainable Food Systems, 2020)
The growing interest in incentivizing sustainable agricultural practices is supported by a large network of voluntary production standards, which aim to offer farmers and ranchers increased value for their product in support of reduced environmental impact. To be effective with producers and consumers alike, these standards must be both credible and broadly recognizable, and thus are typically highly generalizable. However, the environmental impact of agriculture is strongly place-based and varies considerably due to complex biophysical, socio-cultural, and management-based factors, even within a given sector in a particular region. We suggest that this contradiction between the placeless generality of standards and the placed-ness of agriculture renders many sustainability standards ineffective. In this policy and practice review, we examine this contradiction through the lens of beef production, with a focus on an ongoing regional food purchasing effort in Denver, Colorado, USA. We review the idea of place in the context of agricultural sustainability, drawing on life cycle analysis and diverse literature to find that recognition of place-specific circumstances is essential to understanding environmental impact and improving outcomes. We then examine the case of the Good Food Purchasing Program (GFPP), a broad set of food-purchasing standards currently being implemented for institutional purchasing in Denver. The GFPP was created through a lengthy stakeholder-inclusive process for use in Los Angeles, California, USA, and has since been applied to many cities across the country. The difference between Los Angeles’ process and that of applying the result of Los Angeles’ process to Denver is instructive, and emblematic of the flaws of generalizable sustainability standards themselves. We then describe the essential elements of a place-based approach to agricultural sustainability standards, pointing toward a democratic, process-based, and outcome-oriented strategy that results in standards that enable rather than hinder the creativity of both producers and consumers. Though prescription is anathema to our approach, we close by offering a starting point for the development of standards for beef production in Colorado that respect the work of people in place.